2009
DOI: 10.1080/09593330902838080
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐adsorbents for the removal of metallic pollutants from water and wastewater

Abstract: Of the variety of adsorbents available for the removal of heavy and toxic metals, activated carbon has been the most popular. A number of minerals, clays and waste materials have been regularly used for the removal of metallic pollutants from water and industrial effluents. Recently there has been emphasis on the application of nanoparticles and nanostructured materials as efficient and viable alternatives to activated carbon. Carbon nanotubes also have been proved effective alternatives for the removal of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(156 citation statements)
references
References 184 publications
4
148
0
4
Order By: Relevance
“…Carbon nanotubes have been proved effective alternatives for the removal of metallic pollutants from aqueous solutions (Sharma et al 2009). Due to its importance from an environmental viewpoint, special emphasis has been given to the removal of the metals Cr, Cd, Hg, Zn, As, and Cu.…”
Section: Multi-walled Cnts (Mwcnts)mentioning
confidence: 99%
“…Carbon nanotubes have been proved effective alternatives for the removal of metallic pollutants from aqueous solutions (Sharma et al 2009). Due to its importance from an environmental viewpoint, special emphasis has been given to the removal of the metals Cr, Cd, Hg, Zn, As, and Cu.…”
Section: Multi-walled Cnts (Mwcnts)mentioning
confidence: 99%
“…An ideal adsorbent for wastewater treatment purposes should satisfy the following criteria [26]: (1) should be environmentally benign; (2) should demonstrate a high sorption capacity and high selectivity especially to the pollutants occurring in water at low concentration; (3) the adsorbed pollutants can be easily removed from its surface, and (4) should be recyclable. In recent years, many studies have proved that the nanomaterials can satisfy most of these requirements [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Other formation processes are inert gas condensation, spray pyrolysis, laser pyrolysis, flame spray pyrolysis, pulsed laser ablation, spark discharge generation, ion sputtering, photothermal synthesis, thermal plasma synthesis, flame synthesis, low temperature reactive synthesis, mechanical alloying/milling, mechanochemical synthesis, and electro-deposition [43,128]. Li et al [130] recently reported the first mixed-matrix composite membrane made of commercially available poly (amide-b-ethylene oxide) mixed with the nano-sized zeolitic imidazole framework ZIF-7.…”
Section: Recent Progress In Mixed-matrix Nanomembranesmentioning
confidence: 99%
“…The applications of nanoparticles for membranes are usually prepared through the sol-gel process, which yields high-purity samples and allows the control of nanoparticle size, composition, and surface chemistry [128,129]. Other formation processes are inert gas condensation, spray pyrolysis, laser pyrolysis, flame spray pyrolysis, pulsed laser ablation, spark discharge generation, ion sputtering, photothermal synthesis, thermal plasma synthesis, flame synthesis, low temperature reactive synthesis, mechanical alloying/milling, mechanochemical synthesis, and electro-deposition [43,128].…”
Section: Recent Progress In Mixed-matrix Nanomembranesmentioning
confidence: 99%